2021
DOI: 10.1080/09515070.2021.1877620
|View full text |Cite
|
Sign up to set email alerts
|

Activity preferences in psychotherapy: what do patients want and how does this relate to outcomes and alliance?

Abstract: View related articlesView Crossmark data Citing articles: 2 View citing articles Activity preferences in psychotherapy: what do patients want and how does this relate to outcomes and alliance?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
3
9
1
Order By: Relevance
“…We found that directive guidance was especially valued in our sample, acting as a key facilitator for problem solving. This is consistent with previous studies from the PRIDE research group and others across the world, showing that young people favour helping professionals who can provide relatable, age-appropriate information to help with understanding their problems along with concrete advice about coping strategies (Cooper et al, 2021;Gonsalves et al, 2019;Mcarthur et al, 2016;Persson et al, 2017). Preferences for more active therapist input have been interpreted in other research as a sign of readiness to change and as a marker of problem "assimilation," where problems have been brought into conscious awareness and can be actively resolved (Stiles, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…We found that directive guidance was especially valued in our sample, acting as a key facilitator for problem solving. This is consistent with previous studies from the PRIDE research group and others across the world, showing that young people favour helping professionals who can provide relatable, age-appropriate information to help with understanding their problems along with concrete advice about coping strategies (Cooper et al, 2021;Gonsalves et al, 2019;Mcarthur et al, 2016;Persson et al, 2017). Preferences for more active therapist input have been interpreted in other research as a sign of readiness to change and as a marker of problem "assimilation," where problems have been brought into conscious awareness and can be actively resolved (Stiles, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…While this study was narrowly focused on phobias-and broadly at that, not detailing any of the subtypes of phobia but rather the general concept-our findings on the whole contradict recent work endorsing pure therapist directivity (Cooper & Norcross, 2016;Cooper et al, 2019;Cooper et al, 2021). Our findings underscore the sentiment that people desire a gentler, lessintrusive and domineering form of therapy in the treatment of phobias, and add support to the evidence-base around preferences for overarching person-centered approaches to therapy.…”
Section: Implications Of This Study For the Literature And Future Researchcontrasting
confidence: 63%
“…Most recently, Cooper and Norcross (2016) empirically established that clients have preferences for therapist directiveness (versus non-directiveness, actively guiding and interpreting, or not guiding and interpreting, the client; one can consider cognitive-behavioral and person-centered modalities examples); emotional intensity versus emotional reserve (pertaining to therapist style and temperament); past-versus present-focused orientation, referencing whether the therapist encourages discussion of prior or present-moment experiencing; and warm support versus focused challenge (again relating to therapist style). They found, and this has been replicated in further research on the subject (Cooper et al, 2019;Cooper et al, 2021), that clients tend to have a preference for emotional intensity and therapist directivity (whereas mental health professionals tend to prefer client directivity for themselves; Cooper et al, 2021).…”
Section: Furnham (1995) On the Treatment Of Phobias In 2020mentioning
confidence: 79%
“…Subsequent studies found that Western clients tended to prefer therapist directiveness (e.g., learning skills), emotional expression, and focused challenge in their treatment (Cooper et al, 2019; Heinze, Weck, & Kühne, 2022). They also tended to desire treatment that was oriented toward the present (Cooper et al, 2022; Heinze, Weck, & Kühne, 2022).…”
Section: Client Preferences and Measuresmentioning
confidence: 99%
“…However, indirect evidence suggests that there may be preference differences between those two groups. Given their clinical training and experience, non-Western professionals are probably more aware than laypersons of the benefits of emotional expression and focused challenges in psychotherapy (Cooper et al, 2022; Peluso & Freund, 2018), and we therefore predict differences in these dimensions. Further, influenced by Western theories and teachings, Chinese psychotherapists may be unlikely to have a favorable view of therapist directiveness (Duan et al, 2012), but Chinese laypersons may well value it (Duan et al, 2022).…”
Section: Client Preferences and Measuresmentioning
confidence: 99%